2010
DOI: 10.1152/ajpendo.00646.2009
|View full text |Cite
|
Sign up to set email alerts
|

Adipose differentiation-related protein regulates lipids and insulin in pancreatic islets

Abstract: The excess accumulation of lipids in islets is thought to contribute to the development of diabetes in obesity by impairing ␤-cell function. However, lipids also serve a nutrient function in islets, and fatty acids acutely increase insulin secretion. A better understanding of lipid metabolism in islets will shed light on complex effects of lipids on ␤-cells. Adipose differentiation-related protein (ADFP) is localized on the surface of lipid droplets in a wide range of cells and plays an important role in intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
80
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(93 citation statements)
references
References 70 publications
10
80
3
Order By: Relevance
“…These results suggest, respectively, that the herbal blend may attenuate fat accumulation by partially blocking adipogenesis and fat uptake, and by rendering lipid droplets more susceptible to lipases. [23][24][25][26][27][28] The ability of the herbal mix to promote significant weight loss may explain the higher levels of circulating adiponectin observed in the herbal supplemented group. These higher adiponectin levels, in turn, may increase fat metabolism, leading to a reduction in WHR, as adiponectin has been shown to facilitate fat oxidation in skeletal muscle and liver.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest, respectively, that the herbal blend may attenuate fat accumulation by partially blocking adipogenesis and fat uptake, and by rendering lipid droplets more susceptible to lipases. [23][24][25][26][27][28] The ability of the herbal mix to promote significant weight loss may explain the higher levels of circulating adiponectin observed in the herbal supplemented group. These higher adiponectin levels, in turn, may increase fat metabolism, leading to a reduction in WHR, as adiponectin has been shown to facilitate fat oxidation in skeletal muscle and liver.…”
Section: Discussionmentioning
confidence: 99%
“…2). Furthermore, the downregulation of ADFP in MIN6 cells by ASO resulted in the suppression of the TG accumulation upon FFAs loading, indicating that ADFP may participate in the regulation of intracellular lipid metabolism in islet beta cells (Faleck et al, 2010) (Fig. 1).…”
Section: Perilipin Familymentioning
confidence: 94%
“…Moreover, Imai et al reported that the reduction of ADFP via antisense oligonucleotide (ASO) could reverse fatty liver and alter lipid metabolism (Imai et al, 2007). More recently, it was found that the HFa diet could markedly increase the expression level of ADFP in murine islets along with the incremental expression of ADFP in human islets by addition of FFAs (Faleck et al, 2010). Effect of long-term lipotoxicity on the expression/activity of ADFP in beta cells remains to be identified (Fig.…”
Section: Perilipin Familymentioning
confidence: 99%
“…However, somewhat unexpectedly, the effects of both phloretin treatment and FATP4 knockdown to reduce OA uptake by the GLUTag cells were relatively modest compared with their ability to prevent OA-induced GLP-1 release. A similar dissociation between OA uptake and insulin secretion has been noted in mouse insulinoma MIN6 cells such that knockdown of the adipose differentiation-related protein that coats lipid droplets decreases OA uptake by 17% but reduces insulin secretion by more than 50% (12). This discrepancy was attributed to impaired lipid metabolism, although the exact mechanisms were not investigated.…”
Section: Discussionmentioning
confidence: 73%